Ownership structure and dividend per share of listed manufacturing companies in sri lanka - Jeyan Suganya, D.F.; Kengatharan, L. (University of Jaffna, 2018)
The aim of this study was to investigate the relationship between ownership structure and dividend per share of manufacturing companies listed on the Colombo Stock Exchange in Sri Lanka. Institutional ownership, managerial ownership and foreign ownership were considered as explanatory variables while dividend per share was used as response variable. Control variables were firm size and firm leverage. Secondary data were collected from the annual report of 26 randomly selected manufacturing companies for 5 years from 2011 to 2015. Descriptive and inferential statistics were used to analyze the data using SPSS. Results of this study revealed that institutional ownership had significant negative relationship with dividend per share. On the other hand, firm size significantly positively related with dividend per share. Thus it can be used as an alternative tool that can support to minimize the agency problem.
Keywords: Institutional ownership; Managerial ownership; Foreign ownership; Dividend per share